IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 1 MUARO JAMBI - Oktavani, Andrio; Saputra, Edi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Merdeka Curriculum is an educational policy that emphasizes learning flexibility and the strengthening of students’ competencies and character. Its implementation requires teachers to adapt learning planning, instruction, and assessment practices. This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education and Character Education at SMP Negeri 1 Muaro Jambi, identify challenges faced by teachers, and examine efforts to address these challenges. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that SMP Negeri 1 Muaro Jambi began implementing the Merdeka Curriculum in 2023 under the “independent change” category. Teachers encountered several challenges, including difficulties in preparing teaching modules, managing classrooms due to student heterogeneity, differences in students’ interests and talents that complicate differentiated learning, and determining appropriate assessment methods for project-based learning. Limited competence in utilizing information and communication technology also remains a significant obstacle. To overcome these challenges, teachers have participated in curriculum training programs, engaged in peer discussions and sharing best practices, developed adaptive learning tools, and continuously improved their technological competencies. These efforts play an important role in supporting the effective implementation of the Merdeka Curriculum.